Analisis pengelolaan aset tanah Wakaf terhadap kinerja Nazhir menurut hukum Islam dan UU Wakaf - Jejen Jaenudin; Siska Lis Sulistiani; Ramdan Fawzi (Bandung Conference Series: Islamic Family Law, 2025)
Abstract. As a form of worship to get closer to Allah SWT related to property, waqf is very beneficial. There are waqf land assets located in Centeng Village, Cihanjuang Village, Parongpong District, West Bandung Regency, which in its management is carried out by nazhir which is not in accordance with its obligations. So that nazhir as a manager of waqf assets has a role in the management of waqf assets. With that, the performance of the nazhir in managing waqf assets will determine the quality and quantity of the utilization of waqf assets. This study uses a normative juridical approach with a type of qualitative research, data collected by means of interviews and literature studies. Based on the results of the research, the performance of the nazhir towards its duties and obligations is not fulfilled due to the lack of knowledge about the duties of a nazhir, the lack of knowledge about the importance of waqf recording, and the lack of socialization by PPAIW or the government to the community. In Islamic law, the management carried out by the nazhir in Centeng Village, Cihanjuang Village, Parongpong District, West Bandung Regency is not in accordance with Islamic law where the nazhir does not carry out his responsibilities to carry out his duties properly by managing waqf land assets such as not doing records. Then in the Waqf Law, the management carried out by nazhir in Centeng Village, Cihanjuang Village, Parongpong District, West Bandung Regency is not in accordance with what is stated in Law Article 11 No.41 of 2004 concerning waqf. Abstrak. Indonesia adalah negara yang berlandaskan hukum, diberbagai bidang terutama dalam Sebagai salah satu bentuk ibadah untuk mendekatkan diri kepada Allah SWT yang berkaitan dengan harta benda menjadikan wakaf sangat besar manfaatnya. Ada aset tanah wakaf yang terdapat di Kampung Centeng Desa Cihanjuang Kecamatan Parongpong Kabupaten Bandung barat yang mana dalam pengelolaannya yang dilakukan oleh nazhir yang tidak sesuai dengan kewajibannya. Sehingga nazhir sebagai pengelola aset wakaf memiliki peran dalam pengelolaan aset wakaf. Dengan itu kinerja nazhir dalam mengelola aset wakaf akan menentukan kualitas dan kuantitas pemanfaatan aset wakaf. Penelitian ini menggunakan pendekatan yuridis normatif dengan jenis penelitian kualitatif, data yang dikumpulkan dengan cara wawancara dan studi pustaka. Berdasarkan hasil penelitian, kinerja nazhir terhadap tugas dan kewajibannya tidak terpenuhi karena kurangnya pengetahuan akan tugas seorang nazhir, kurangnya pengetahuan tentang pentingnya pencatatan wakaf, dan kurangnya sosialisasi oleh PPAIW ataupun pemerintah kepada masyarakat. Dalam hukum Islam pengelolaan yang dilakukan nazhir di Kampung Centeng Desa Cihanjuang Kecamatan Parongpong Kabupaten Bandung barat tidak sesuai dengan hukum Islam dimana nazhir tidak melakukan tanggung jawab untuk menjalankan tugasnya dengan baik dengan cara mengelola aset tanah wakaf seperti tidak melakukan pencatatan . Kemudian dalam UU Wakaf, pengelolaan yang dilakukan nazhir di Kampung Centeng Desa Cihanjuang Kecamatan Parongpong Kabupaten Bandung barat tidak sesuai dengan apa yang di sebutkan dalam UU Pasal 11 No.41 Tahun 2004 tentang wakaf.